Comparative Scorecard Assessment of Urban Water Pricing Policies—The Case of Jordan and Iran - Mohammad Al-Saidi (5751827) (2019)
Urban water pricing is becoming increasingly important due to the rapid rate of urbanization and the expansion of water reclamation and reuse. The mounting evidence of failures of current pricing schemes makes analyzing their performance essential for understanding the adequacy of economic and sustainability policies in water management. However, urban water pricing policies are complex, serve multiple objectives, and vary widely across regions and countries. This paper presents an assessment framework for urban water pricing policies based on common conditions advocated for well-functioning pricing policies. Using a simplified scorecard, it compares the performance of urban water pricing policies in Jordan and Iran, two countries under growing scarcity pressure. Both countries show serious deficiencies with regard to the economic valuation of water services and the cost recovery of utilities. Public policies are rather oriented towards access and affordability, with Jordan showing a higher level of transparency and competition in tariff-setting. The assessment tool indicates a high potential for experience-sharing in future reforms, which should promote water as a scarce good. Such reforms need to prioritize full cost valuation, participation, and scientifically based designs of local and regional water tariffs. Other Information Published in: Water License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/w11040704